Prosthetic rehabilitation of a young patient with Hypophosphatasia - A review and case report - Partapjot S Grewal; Kanu Priya Gupta (Wolters Kluwer Medknow Publications, 2012)
Hypophosphatasia is a congenital disease characterized by deficiency of serum and tissue non-specific alkaline phosphatase activity. The disease occurs due to mutations in the liver/bone/kidney alkaline phosphatase gene. Six clinical forms of hypophosphatasia are recognized. Systemic symptoms of the disease are respiratory complications, premature craniosynostosis, widespread demineralization and rachitic changes in the metaphases, stress fractures, chondrocalcinosis and osteoarthropathy. Characteristic dental symptoms include premature loss of deciduous teeth, premature exfoliation of fully rooted permanent teeth, severe dental caries and alveolar bone loss. This clinical report describes the prosthetic rehabilitation of a sixteen year old female patient with hypophosphatasia with partial anodontia and no occlusion. Patient was managed clinically by saving her remaining teeth, fabricating a maxillary overdenture and mandibular cast partial denture. This not only helped her functionally in biting and chewing food and achieving a good occlusion, but also restored her confidence and self image by improving the aesthetics.